Correlation between drying defects, their parameters and moisture gradient in kiln-dried, south african grown Eucalyptus Grandis poles - Mugabi, P.; Rypstra, T.; Vermaas, H.F.; Nel, D.G. (Maderas. Ciencia y Tecnología, 2025)
Non-destructive testing for drying defects in Eucalyptus grandis utility poles would be highly advantageous. These defects can negatively affect creosote preservative treatment and in-service performance. The objective of this study was to assess correlations between drying defects such as surface checking, honeycombing, collapse, their parameters and moisture content (MC) gradient in poles, to possibly find a simple and quick but reliable method to assess internal and external drying defects. Defects and moisture content gradients were measured in 39 kiln-dried E. grandis poles. After measuring surface check length, width and depth using a measuring tape, a ruler and a depth gauge, destructive sampling at the theoretical ground line (TGL) was done to measure the MC gradient between the shell and core of poles. Digital image analysis of cross-sections of discs cut at TGL was used to measure honeycomb check width, length and area, as well as counting individual closed surface checks. Collapse was assessed using qualitative methods. Results showed that honeycombing and collapse were positively, and surface checking and MC gradient were negatively correlated. Surface check width, length and depth were also correlated. Honeycomb count, check width, length and area were strongly correlated. It was concluded that measuring any of these surface check and/or honeycomb parameters may give meaningful deductions about the extent of surface checking and honeycombing respectively.